2018
DOI: 10.1186/s41155-018-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

The Dusseldorf Illustrated Schema Questionnaire for Children (DISC)

Abstract: Childhood experiences are considered to be of crucial importance in the formation of maladaptive schemas, according to Young's concept. Although some schema questionnaires already exist for children, these instruments differ in their schema structures with between 8 and 12 identified factors. To obtain a deeper understanding of early maladaptive schemas in childhood an instrument based on Young's 18-schema model was constructed (Dusseldorf Illustrated Schema Questionnaire for Children (DISC)). Cartoons were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 42 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…In the original study by Loose et al, (2018a, b), Cronbach's alpha level for the internal consistency of scale was found to be 0.87 and test-retest reliability was r = 0.61 (p < 0.001) at 12-to 13-month intervals and r = 0.37 (p < 0.05) at 26-to 34-month intervals. Corresponding schemas of the DISC and the SIC were found to be positively correlated (ranging between 0.22 and 0.69, p < 0.001) indicating criterion validity (Loose et al, 2018b). Pearson's r correlations of the DISC with Strengths and Difficulties Questionnaire (SDQ, Goodman, 1997) for predictive validity indicated that the correlation was r = 0.42 (p < 0.001) with the self-assessment version of the SDQ and it was r = 0.23 (p < 0.001) with the parent assessment version of the SDQ (Loose et al, 2018b).…”
Section: Data Collection Toolsmentioning
confidence: 87%
See 3 more Smart Citations
“…In the original study by Loose et al, (2018a, b), Cronbach's alpha level for the internal consistency of scale was found to be 0.87 and test-retest reliability was r = 0.61 (p < 0.001) at 12-to 13-month intervals and r = 0.37 (p < 0.05) at 26-to 34-month intervals. Corresponding schemas of the DISC and the SIC were found to be positively correlated (ranging between 0.22 and 0.69, p < 0.001) indicating criterion validity (Loose et al, 2018b). Pearson's r correlations of the DISC with Strengths and Difficulties Questionnaire (SDQ, Goodman, 1997) for predictive validity indicated that the correlation was r = 0.42 (p < 0.001) with the self-assessment version of the SDQ and it was r = 0.23 (p < 0.001) with the parent assessment version of the SDQ (Loose et al, 2018b).…”
Section: Data Collection Toolsmentioning
confidence: 87%
“…Corresponding schemas of the DISC and the SIC were found to be positively correlated (ranging between 0.22 and 0.69, p < 0.001) indicating criterion validity (Loose et al, 2018b). Pearson's r correlations of the DISC with Strengths and Difficulties Questionnaire (SDQ, Goodman, 1997) for predictive validity indicated that the correlation was r = 0.42 (p < 0.001) with the self-assessment version of the SDQ and it was r = 0.23 (p < 0.001) with the parent assessment version of the SDQ (Loose et al, 2018b). In the current study, Cronbach's alpha of the total score was 0.89 and it ranged between 0.42 and 0.83 for the subscales.…”
Section: Data Collection Toolsmentioning
confidence: 87%
See 2 more Smart Citations
“…And they identified features (closeness, eigenvector, and centrality) which boost stress level only in adults. As children grow they should adjust for each new environment, it is important too, work [6] describes developments in children while asking questions by designing schemas, and special case children were not included in homogeneous sampling. Using Deep Belief Network and greedy method Saeed [7] proved there is a maximum ADHD prediction accuracy can be achieved and that can be compared to other methods.…”
Section: A Summary Of Adhd Based On Attentionmentioning
confidence: 99%